Способ симультанной трансабдоминальной видеолапароскопической левосторонней адреналэктомии и холецистэктомии - Завгородний, С. Н.; Кубрак, М. А.; Данилюк, М. Б.; Рылов, А. И.; Завгородній, Сергій Миколайович; Кубрак, Михайло Анатолійович; Данилюк, Михайло Богданович; Рилов, Андрій Іванович (Norwegian Journal of development of the International Science, 2018)
Urgency. The existing methods of simultaneous videolaparoscopic treatment of combined pathology of the adrenal glands and cholelithiasis have a number of disadvantages. All this caused the need to develop new ways of simultaneous videolaparoscopic treatment of these pathologies. Purpose of research. To improve the results of surgical treatment of patients with a combination of left adrenal pathology and gastrointestinal tract. Materials and methods. During the period from 2014 to 2018, 8 simultaneous videolaparoscopic leftside adrenalectomies and cholecystectomies were performed. Among the operated 7 (87.5 %) women and 1 (12.5 %) man. The mean age of patients was 48.6 ± 13.7 years. The comparison group included 3 (37.5 %) patients who underwent surgery according to conventional methods. The main group included 5 (62.5 %) patients who underwent surgery according to the developed method. Research result. The average duration of surgery in the main group was 98.4 ± 16.1 minutes, in the comparison group 112.7 ± 21.3 minutes (p ˂ 0.05). The increase in blood pressure was observed in the main group to 57.5 ± 15.6 minutes, and in the observation group to 86.1 ± 13.3 minutes of surgery (p ˂ 0.01). The average duration of hospitalization of patients of the main group was 9.4 ± 3.1 days. In the comparison group, and 11.2 ± 3.7 days (p < 0.05). Conclusions: Videolaparoscopic adrenalectomy and cholecystectomy is a method of choice of surgical treatment of patients with combined adrenal pathology and cholelithiasis. Актуальность. Существующие способы симультанного видеолапароскопического лечение сочетанной патологии надпочечников и желчнокаменной болезни (ЖКБ) имеют ряд недостатков. Все это вызвало необходимость в разработке новых способов симультанного видеолапароскопического лечения этих патологий. Цель исследования. Улучшить результаты хирургического лечения больных с сочетанием патологии левого надпочечника и ЖКБ. Материалы и методы. За период с 2014 по 2018 год выполнено 8 симультанных видеолапароскопических левосторонних адреналэктомий и холецистэктомий. Среди прооперированных 7 (87,5 %) женщин и 1 (12,5 %) мужчин. Средний возраст пациентов составил 48,6 ± 13,7 лет. В группу сравнения вошло 3 (37,5 %) больных, которым выполнено оперативное вмешательство по общепринятой методике. Основная группа включала 5 (62,5 %) пациентов, которым проведена операция согласно разработанного способа. Результаты. Средняя продолжительность оперативного вмешательства в основной группе составила 98,4 ± 16,1 минуты, в группе сравнения 112,7 ± 21,3 минуты (р ˂ 0,05). Повышение артериального давления (АД) наблюдалось в основной группе до 57,5 ± 15,6 минут, а в группе наблюдения до 86,1 ± 13,3 минуты оперативного вмешательства (р ˂ 0,01). Средняя продолжительность госпитализации пациентов основной группы составила 9,4 ± 3,1 дня. В группе сравнения – 11,2 ± 3,7 дня (р ˂ 0,05). Выводы: Видеолапароскопическая адреналэктомия и холецистэктомия является методом выбора оперативного лечения больных с сочетанной патологией надпочечников и желчнокаменной болезнью.
Method of simultaneous transabdominal videolaparoscopic leftside adrenalectomy and cholecystectomy
Keywords: cholecystectomy; adrenalectomy; simultaneous operations; холецистэктомия; адреналэктомия; симультанные операции